Cardiac index-guided therapy to maintain optimised postinduction cardiac index in high-risk patients having major open abdominal surgery: the multicentre randomised iPEGASUS trial - Funcke, Sandra; Schmidt, Götz; Bergholz, Alina; Argente Navarro, Pilar; Azparren Cabezón, Gonzalo; Barbero-Espinosa, Silvia; Diaz-Cambronero, Oscar; Edinger, Fabian; García-Gregorio, Nuria; Habicher, Marit; Klinkmann, Gerd; Koch, Christian; et al. (British journal of anaesthesia : BJA, 2024)
It is unclear whether optimising intraoperative cardiac index can reduce postoperative complications. We tested the hypothesis that maintaining optimised postinduction cardiac index during and for the first 8 h after surgery reduces the incidence of a composite outcome of complications within 28 days after surgery compared with routine care in high-risk patients having elective major open abdominal surgery. In three German and two Spanish centres, high-risk patients having elective major open abdominal surgery were randomised to cardiac index-guided therapy to maintain optimised postinduction cardiac index (cardiac index at which pulse pressure variation was <12%) during and for the first 8 h after surgery using intravenous fluids and dobutamine or to routine care. The primary outcome was the incidence of a composite outcome of moderate or severe complications within 28 days after surgery. We analysed 318 of 380 enrolled subjects. The composite primary outcome occurred in 84 of 152 subjects (55%) assigned to cardiac index-guided therapy and in 77 of 166 subjects (46%) assigned to routine care (odds ratio: 1.87, 95% confidence interval: 1.03–3.39, P=0.038). Per-protocol analyses confirmed the results of the primary outcome analysis. Maintaining optimised postinduction cardiac index during and for the first 8 h after surgery did not reduce, and possibly increased, the incidence of a composite outcome of complications within 28 days after surgery compared with routine care in high-risk patients having elective major open abdominal surgery. Clinicians should not strive to maintain optimised postinduction cardiac index during and after surgery in expectation of reducing complications. NCT03021525.